Studi Penanggulangan Banjir Krueng Tripa - Meliyana Meliyana; Ichsan Syahputra; Andhika Mahbengi; Cut Rahmawati (Jurnal Teknik Sipil Unaya, 2018)
Krueng Tripa is located in 2 (two) regencies, namely Gayo Lues and Nagan Raya with total area of catchmen area is ± 3,472.95 Km2. The rainfall that affects Krueng Tripa watershed ranges from 493 mm up to 2,197 mm per year. the high rainfall effect on flood events that have caused adverse impacts on the lives of people along the river. The purpose of this study is to estimate peak flood discharge and to propose  flood control management. Analysis flood discharge using with Synthetic Unit Hydrograph (HSS) Soil Conservation Service (SCS).  The rainfall data test show that the rainfall distribution tend to follow the Gumbel, with the rate of design rainfall for 25-year return period to be 154,49 mm/day. Analysis of river flood discharge Krueng Tripa obtained Q25 = 3151,742 m3/s. The control flood recommendation of Krueng Tripa can be accomplished is a dam as flood control structure at the upstream of the river. Result of level pool routing obtained outflow hydrographs  2762,854 m3/s, resulting in a discharge reduction of 388.88 m3/s.